Schleichera oleosa (Kusum) leaf extract mediated green synthesis of bimetallic Ag-Fe nanoparticles: in-vitro evaluation of antimicrobial and antioxidant activities - Divyanshu Singh; Dimpi Gupta; Ankit Tiwari; Jai Naik; Farheen Quraishi; Rajat Pratap Singh; Sunil Kumar Singh; Ashish Kumar Singh (Discover Applied Sciences)
Abstract Using plant extracts for nanoparticle synthesis represents a green, straightforward and cost-effective approach. Recent studies suggest that combining transition metals can result in synergistic antimicrobial and antioxidant properties. This work describes the green synthesis of Ag-Fe nanoparticles using an aqueous extract of Schleichera oleosa as a reducing and stabilizing/Capping agent. The formation of Ag-Fe NPs is confirmed through different characterization techniques such as Ultraviolet–visible spectroscopy, X-ray diffraction, scanning electron microscope and electron dispersive X-ray spectroscopy, transmission electron microscopy and X-ray photoelectron spectroscopy. Furthermore, Fourier Transform Infrared Spectroscopy was utilized to recognize the specific functional groups associated with phytochemicals which is responsible for the enhanced stability and biological activity of nanoparticles. X-ray diffraction as well as electron microscopic analysis suggests formation of crystalline face-centered cubic Ag-Fe NPs with sizes ranged 16–55 nm. X-ray photoelectron spectroscopy indicates silver may be present in form of metallic silver as well as silver oxide and the satellite peak for iron indicate the presence of Iron in + 2 and + 3 both oxidation states. Antimicrobial activity towards both Gram-positive Bacillus subtilis (MTCC441), Staphylococcus aureus (MTCC96), and Gram-negative Escherichia coli (MTCC739), Pseudomonas aeruginosa (MTCC741) and Klebsiella pneumoniae has been explored using Agar well diffusion method. Ag-Fe nanoparticles exhibit better antimicrobial activity compared to monometallic Ag or Fe or physical mixture of Ag and Fe nanoparticles. Exploration of synergistic Ag-Fe nanoparticles as an effective antimicrobial agent opens a door for biomedical applications of nanoparticles using an environmental-friendly approach. In vitro Antioxidant activity has also been explored using DPPH assay. Contrary to antimicrobial activity, the best antioxidant activity has been exhibited by Plant Extract (92.33 ± 2.88%) followed by Ag (91.58 ± 3.25%,), Fe (91.5 ± 3.88%) and Ag-Fe (89.59 ± 1.92%). These findings are important as they demonstrate the potential of S. oleosa in the green synthesis of metal nanoparticles. This approach not only offers an eco-friendly alternative but also provides a platform for improving biological activity by tuning metal precursors, reaction conditions and other synthesis parameters.